Analisis Efektivitas Mesin Welding di PT Otscon Safety Indonesia dengan Metode Overall Equipment Effectiveness - Delia Febriyanti; Wahyudin Wahyudin; Novi Yanti (Jurnal Serambi Engineering, 2022)
Abstract The fast advancement of the business makes organizations are expected to keep on being useful with great quality. In this manner, the organization should have the option to keep up with each component connected with creation including machines. As one of the primary parts of creation, machines should be kept up with so their efficiency abilities are kept up with and work runs successfully. This study meant to break down the adequacy of welding machine execution through Total Productive Maintenance (TPM) at PT. Otson Safety Indonesia. The technique utilized is Overall Equipment Effectiveness (OEE) with three estimation pointers, in particular accessibility, execution proficiency, and nature of item. The examination was done in the period June-December 2021 which comprised of information on the quantity of creation, deficient items, margin time, and arranged free time. The outcomes got are the typical OEE worth of 58.07 with a piece of 96.56% accessible rate, 89.27%% execution rate, and 95.65% quality rate. The outcomes show that the OEE esteem is still far beneath the world norm, and from the three OEE pointers just the accessible rate is in the norm, while the exhibition rate and quality rate are underneath the norm. From these outcomes, it is important to make enhancements to expand the viability of the presentation on the welding machine.Keywords: Machinery, Productivity, TPM, Manufacturing, OEE. AbstrakPesatnya kemajuan bisnis membuat organisasi diharapkan untuk terus bermanfaat dengan kualitas yang baik. Dengan cara ini, organisasi harus memiliki pilihan untuk mengikuti setiap komponen yang terkait dengan pembuatan termasuk mesin. Sebagai salah satu bagian utama dari penciptaan, mesin harus dijaga agar kemampuan efisiensinya tetap terjaga dan pekerjaan berjalan dengan sukses. Penelitian ini bertujuan untuk mengetahui kecukupan pengerjaan mesin las melalui Total Productive Maintenance (TPM) di PT. Otson Safety Indonesia. Teknik yang digunakan adalah Overall Equipment Effectiveness (OEE) dengan tiga petunjuk estimasi, yaitu aksesibilitas, kemampuan eksekusi, dan sifat item. Pemeriksaan dilakukan pada periode Juni-Desember 2021 yang terdiri dari informasi jumlah pembuatan, kekurangan barang, margin time, dan waktu luang yang diatur. Hasil yang didapat adalah nilai OEE biasa sebesar 58,07 dengan tingkat akses 96,56%, tingkat eksekusi 89,27%%, dan tingkat kualitas 95,65%. Hasil penelitian menunjukkan bahwa nilai OEE masih jauh di bawah norma dunia, dan dari ketiga petunjuk OEE tersebut hanya tarif yang dapat diakses yang masih dalam batas normal, sedangkan tingkat pameran dan kualitas yang berada di bawah norma. Dari hasil tersebut maka perlu dilakukan penyempurnaan untuk memperluas kelayakan penyajian pada mesin las.Kata Kunci: Mesin, Produktivitas, TPM, Manufaktur, OEE